Changes in the German Wage Structure: Unions, Internationalization, Tasks, Firms, and Worker Characteristics - Martin Biewen; Matthias Seckler (Institute of Labor Economics (IZA), 2017)
This paper provides a comprehensive assessment of the quantitative importance of the factors associated with the rise in male wage inequality in Germany over the period 1995 2010. In contrast to most previous contributions, we rely on the German Structure of Earnings Surveys (GSES) which allow us to focus on hourly wages (rather than daily earnings) uncensored by the social security contributions threshold. We consider a large number of covariates including personal characteristics, measures of internationalization, task composition, union coverage, industry, region, and firm characteristics. Our results suggest that recent changes in the distribution of hourly wages in Germany look different from the polarizing patterns found for the US, and that most of the observed rise in inequality was associated with compositional effects of de-unionization and personal characteristics. We also find some moderate effects linked to internationalization, firm heterogeneity and regional convergence, but these were much smaller.
Keywords: C14; J31; J51; F16; 330; RIF regression; reweighting; skill-biased technical change; de-unionization